Institutional angle mark of territorial clustering of natural and economic formations on innovation hubs basis (Economics and region, 2018)
In this article we have determined that the cluster-based innovation hubs - one of the key drivers of economic growth in the country, provides a comprehensive system to support economic and technological interdependence. We found that in recent decades the idea of creating clusters found its application in virtually all countries: EU, US, Japan, South America, Eastern Europe and Africa. Today cluster model is one of the most effective forms of achieving competitive advantage. We have determined that at this time in Ukraine created conditions for the formation of new types of cluster naturally territorial and economic entities. It is important that the process of decentralization of territorial administration provide impetus for a renewed perception of certain theoretical positions clustering economic space. In particular, project management positions natural resource capital. Thus, with the creation of clusters and providing primarily financial component operation must take into account aspects: production, investment and spatial. The production structure of corporate cluster should have an advantage over other forms of economic institutions, such as branches, technological institutions and others. In content, innovative cluster-based innovation hub must have a membership; centers generate scientific knowledge, business ideas, training centers highly qualified specialists and innovators. The activities of this cluster should be aimed at working with promising market innovation. Innovative clusters on the basis innovation hubs should be viewed as promising «growth point of the innovation economy». The basis of their activity is innovator-man. We prove that innovation hub task should be to create favourable conditions for the development of innovative projects that enhance quality of life. For this reason, innovative designs hub necessarily characterized by opportunities in new ways; ways to solve problems of ecological character and key economic sectors (transport, health, energy, housing, social security, education).
Keywords: innovative economy; institutional perspective; naturally territorial and economic formation; innovation hub; innovation cluster